Enteric-coated insulin microparticles delivered by lipopeptides of iturin and surfactin - Xiaoying Xing; Xiuyun Zhao; Jia Ding; Dongming Liu; Gaofu Qi (Taylor & Francis Group, 2018)
Surfactin, a lipopeptide produced by Bacillus species, has been used for the oral delivery of insulin. In this study, another lipopeptide of iturin was tested for its ability to orally delivery insulin alone or plus surfactin. Iturin could form co-precipitate with insulin at acidic pH values. After treatment by ultrasonification, the structure of coprecipitate was destroyed that led to a significant decrease in hypoglycemic effect after oral administration. Iturin weakly binds to (Kd = 257 μM) and induce insulin structure more compact that is favorable for insulin uptake by the intestine. After being coated with Acryl-Eze by lyophilization, the coprecipitate formed the spherical enteric-coated insulin microparticles delivered by iturin with a relative oral bioavailability of 6.84% in diabetic mice. For further improving oral hypoglycemic effect, surfactin was added to form the spherical enteric-coated insulin microparticles in a formulation containing insulin, Acryl-Eze, iturin and surfactin at a ratio of 1:1:0.5: 0.5 (w/w), with an insulin encapsulation efficiency of 66.22%. The enteric-coated insulin microparticles delivered by iturin plus surfactin showed a classical profile for controlled release in the intestine with a relative bioavailability of 7.67% after oral administration, which could effectively control the postprandial blood glucose at a level about 50% of the initial one just like the subcutaneous injection. Collectively, iturin plus surfactin is more efficient for oral delivering insulin than the sole one, and the resultant enteric-coated insulin microparticles are potential for the development of oral insulin to control postprandial blood glucose in diabetic patients.